A dive into barophysiology research: an interview with Ingrid Eftedal (Communications Biology)
Ingrid Eftedal is a senior scientist at Norwegian University of Science and Technology Department of Circulation and Medical Imaging, Norway, and a leading expert in baromedicine. In this Q&A, we talk about what started her career and the challenges of conducting niche research.